Odpowiedzi

2010-03-07T22:47:51+01:00
A)
0,2x + 0,3 = -0,5
0,2x=-0,5-0,3
0,2x=-0,8
x=-4

b)
0,4 + 0,25x = -2
0,25x=-2-0,25
0,25x=-2,25
x=-9

c)
2,1 - 0,3x = 0,4x
-0,3x-0,4x=-2,1
-0,7x=-2,1
x=3

d)
-1,5x - 3 = 0,2x +6
-1,5x-0,2x=6+3
-1,7x=9
x=-5⁵/₁₇

e)
1/2x - 4 = x - 6
½x-x=-6+4
-½x=-2
x=4

f)
x - 5 = 1/3x + 1
x-⅓x=1+5
⅔x=6
x=9

g)
x/4 - ¼ = 2|*4
x=8+1
x=9


h)
x/5 - 3 = x + 1/5|*5
x-15=5x+1
x-5x=1+15
-4x=16
x=-4

i)
5/6 * (x-1)=4
⅚x-⅚=4
⅚x=4+⅚
⅚x=4⅚
x=5,8

j)
-½(-x - 6) = -x
½x+3=-x
½x+x=-3
1½x=-3
x=-2